Editorial - Pacheco Romero, José (2014)
The number of journal articles and technology-including the fields of physics, biology, chemistry, mathematics, clinical medicine, biomedical research, engineering and medical technology, and earth sciences and space-which have been published since 1980 in various countries of the world, according to the database of the World Bank, contained in its website data (1). It is found that the number of articles published by Peru were 159 between 1999 and 2003, 147 between 2004 and 2008 and 162 between 2009 and 2013.